Theory of planned behavior and value-belief norm theory as antecedents of pro-environmental behaviour: Evidence from the local community - Batool, Nusrat; Wani, Mehraj Din; Shah, Shamim Ahmad; Dada, Zubair Ahmad (Journal of human behavior in the social environment, 2024)
Native residents are indispensable participants in developing and conserving the natural environment. Specifying the factors that lead to responsible behavior among the local people can help increase sustainability. This paper aims to investigate the pro-environmental behavior among the local residents of the Kashmir region defined by the components of Theory of Planned Behavior (TPB) and Value Belief Norm (VBN) Theory. To analyze the data, Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM) has been used as research methods. The results reveal that the three components of TPB (general environmental attitude, subjective norms, perceived behavior control) have a positive and significant impact on the pro-environmental behavior of residents. Moreover, the findings also demonstrate that the factors of VBN (altruistic, egoistic and biospheric values) significantly influence the general environmental attitude which in turn impacts the pro-environmental behavior of local residents. The paper seeks to contribute to the existing literature by adding local community insights based on the explanations given by socio-psychological theories within the context of natural environment. The study will help policymakers to understand better the residents' intentions and pro-environmental behavior so that they can develop strategies to manage and combat the environmental problems.